(untitled) (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: This study was conducted to investigate patients perceived barriers to rehabilitation. Methods: A qualitative study was designed using grounded theory and inductive approach that included a semi-structured interview checklist concerning patientsâ€™ perceived barriers to physical therapy service. The transcript was analyzed using ATLAS.ti software and a thematic analysis was conducted. Codes were generated and analyzed by semantic linkages and network analysis. Results: A total of five themes were identified from qualitative analysis, namely, â€œtreatment results pain,â€ â€œout-of-pocket expenditure,â€ â€œlow perceived value for money,â€ â€œunavailability of caregiver,â€ and â€œunavailability of the therapist.â€ Conclusion: Apart from the barriers identified, a novel finding was the perception of intergender treatment as a barrier by female patients. This phenomenon not only has social implications that may contribute adversely to clinical goals for that patient.